Contrasting female mate preferences for red coloration in a fish. Issue 4 (18th October 2019) - Reuland, Charel; Culbert, Brett M; Devigili, Alessandro; Kahrl, Ariel F; Fitzpatrick, John L
Abstract: Understanding how animals select their mates requires knowing the factors that shape mate preferences. Recent theoretical and empirical considerations suggest that female mating status can influence the degree to which a female engages in mate choice, with virgin females predicted to be less choosy than mated females. In this study, we investigated mate choice in both virgin and mated females in the pygmy halfbeak Dermogenys collettei . Halfbeaks are small, live-bearing, internally fertilizing freshwater fish that live in mixed-sex groups where females have ample opportunity to engage in mate choice. Using a dichotomous choice assay, we quantified and contrasted in virgin and mated females mate preferences for differences in male body size, beak size, and area of yellow and red coloration. We also examined how mating status influenced the amount of time a female associated with the first male encountered and the relative amount of time a female associated with each male. We demonstrate that mate preferences of female halfbeaks are driven primarily by the size of red coloration present on males. Females showed contrasting preferences based on mating status, with virgin females preferentially associating with drab males whereas mated females preferentially associate with males possessing large areas of red. Contrary to expectations, female mating status did not influence how females associate with the first males encountered or how females biased their association time among males. Although the precise drivers of these effects need further studying, our finding highlights a possible explanation for how variation in male ornamentation can be maintained.